Psychosocial work factors and anxiety and depression symptoms in the intensive care unit of a public hospital in Nuevo Chimbote - Trujillo Ulloa, Washington Alfonso (2024)
Objective: To determine the association between psychosocial work factors and anxiety or depression symptoms among health workers of the Intensive Care Unit (ICU) at Hospital Regional Eleazar Guzmán Barrón in Nuevo Chimbote. Materials and methods: The study used a quantitative, observational, non-experimental, cross-sectional and descriptivecorrelational research design. The population consisted of 70 workers of the hospital’s ICU. A census sampling and survey technique were employed. The instruments were the following: Questionnaire on Psychosocial Work Factors Administered to Peruvian Workers, validated with a Cronbach’s alpha coefficient of 0.9; Lima Anxiety Scale (EAL-20), validated with a Cronbach’s alpha coefficient of 0.89; and Psychopathology Scale for Depressive Disorders (EPD-6), validated with a Cronbach’s alpha coefficient of 0.7359. By applying descriptive statistics, IBM SPSS Statistics V26 was used for data collection, processing and analysis, and the chi-square test for the association of variables. Results: The lowest psychosocial work factor was work role and career development (57.10 %), with the nursing staff being the most affected one (27.10 %). The highest psychosocial work factor was performance-based remuneration (40.00 %), with the technical nursing staff being the most affected one (30.00 %). Conclusions: Working conditions, workload, work demands and content and characteristics of the task were the work dimensions associated with the occurrence of anxiety symptoms; likewise, content and characteristics of the task, work demands, and work role and career development were the dimensions associated with the occurrence of depression symptoms.